The art of hearing: English preachers and their audiences, 1590 - 1640 - Hunt, Arnold 19XX- (Cambridge studies in early modern British history, 2010)
Throughout Christian history the sermon has been a key means of transmitting religious ideas. This book assesses the effectiveness of the sermon as a means of spreading Protestant ideas in early modern England by focusing on how sermons were interpreted by their audience